The Influence of the Blended Learning Model on Fifth-Grade Students’ Motivation in Physical Education at SD Aisyiyah Sukabumi - Lau, Bachtiar; Sauri, Sopian; Saleh, Muhammad; Nugraheni, Wening; Tuti Lestari, Ade (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective :This study aims to examine the effect of the blended learning model on learning motivation in physical education for fifth-grade students at SD Aisyiyah, Sukabumi. Method: The research employed a quantitative pre-experimental design using a One-Group Pretest-Posttest Design. The population consisted of all fifth-grade students, and a sample of 21 students was selected using cluster random sampling within a probability sampling framework. The data were analyzed using descriptive statistics and a paired-sample t-test. The collected data were analyzed using descriptive statistics and a paired sample t-test. Results: The analysis demonstrated an increase in student learning motivation after the implementation of blended learning. The pretest produced a mean score of 27.04 (SD=9.255), while the posttest mean score increased to 38.00 (SD=3.619). The paired-sample t-test yielded a significance value of 0.000 (<0.05), that the blended learning model had a significant effect on students’ learning motivation. Novelty: This study contributes to the existing literature on blended learning by emphasizing its effectiveness in enhancing motivation in physical education, an area that often receives less attention compared to academic subjects. The findings offer empirical evidence that blended learning can be a valuable approach in elementary school to promote students’ engagement and motivation in physical activity learning.